Professional Exam: Assessing Teachers' Qualifications According to Requirements of Professional Standard - Minyurova S.A; Leonova O.I (Moscow State University of Psychology and Education, 2016)
This paper focuses on the issues of applying professional standards for preschool and school teachers in the assessment of teachers' qualifications and the development of their professional skills. The paper reviews foreign practices in the subject and approaches to the organization of qualification exams for teachers in various countries. The discussed issues include the development of such criteria for assessing the quality of teaching activity that would promote professional skills in teachers as well as reveal the outcomes of this activity in students. The paper concludes with an outline of the key elements of the model of professional exam for teachers as a form of assessment aiming to prove that teachers' qualifications meet the requirements of the professional standard.